An assessment of available Potassium (K) distribution in oil palm plantation. A case study on Acid Sulfate Soil (ASS) / Mohamad Amiruddin Abdullah - Abdullah, Mohamad Amiruddin (Faculty of Plantation and Agrotechnology, 2017)
This study was conducted to observe the availability of potassium (K) distribution in oil palm plantation, specifically on acid sulfate soil (ASS). This study and analysis was conducted at UiTM (Melaka) Jasin Campus starting from September to October 2016. Thirty soil sample were collected at the oil palm plantation on ASS in Merlimau, Melaka located at coordinate of 2°7'43.989"N 102°26'12.45"E. The soil samples were taken at the depth of 0 – 15 cm. Chemical properties such as soil pH, organic matter (OM), total organic carbon (TOC) and available nutrients contents like potassium (K), calcium (Ca) and magnesium (Mg) was determined. The range of soil pH is between 2.43 to 3.98. The range of OM is between 0.6248% to 5.0813. The range of K is between 596.8 mg kg-1 to 1115.8 mg kg-1. The Ca content is between 99.63 mg kg-1 to 1095.00 mg kg-1 while Mg is between 50.820 mg kg-1 to 402.200 mg kg-1.The results showed that pH is 3.19, organic matter is 3.3357%, total organic carbon is 0.0193%, K is 300.76 mg kg-1, Ca is 382.67 mg kg-1 and Mg is 138.92 mg kg-1. Data analysis is performed by using correlation in Minitab software. Based on results from the analysis, there is no significant correlations between the content of available K with the other soil chemical properties.